Perubahan Sosial Kultural Masyarakat Pedesaan (Suatu Tinjauan Teoritik-Empirik) - Arrizal Diwa Muzzaki; Akhmad Fatoni; Andhita Risko Faristiana (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Socio-cultural change is a topic of interest to social scientists and the general public. Awareness of the importance of studying socio-cultural change increases with the rapid development of science and technology. Both urban and rural communities experience changes and developments due to technology, communication and transportation. Social change is an inevitable phenomenon in society. Balgat village is an interesting example to study social change. This paper analyzes social change in Balgat village using the theoretical approaches of modernization, social transformation, social conflict, mass communication, and cultural change. The research method used is a literature study to collect data that is analyzed with valid methods. The results of the study provide insight into the socio-cultural changes in Balgat village, including the role of urbanization, literacy, and media consumption. Analysis with a structural functionalism approach helps to understand the relationship of social change with the community system. In conclusion, social change in Balgat village is understood through a multifactorial approach and structural functionalism theory, making an important contribution to understanding socio-cultural change in the village.